IMMUNOMORPHOLOGICAL FEATURES OF IDIOPATHIC EPIRETINAL MEMBRANES COMPLICATED BY LAMELLAR MACULAR HOLE - U. R. Altynbaev; A. I. Lebedeva (Oftalʹmologiâ)
Objective: Comparative morphological characteristic and evaluation of cytokine profile of idiopathic epiretinal membrane (ERM), complicated lamellar macular hole. Materials and Methods: Immunohistochemical study of 15 ERM removed during vitrectomy included the definition of responses to antigens fibronectin, laminin, glial fibrillary acidic protein. All membrane samples were divided into two groups: I group consisted of 8 ERM, which wasn’t clinically combined with retina defects, the II group included 7 ERM complicated lamellar macular hole. Results: ERM in group I were a collagen-membrane with a thickness from 2,1±0,7 to 4,4±1,4 µm, infiltrated radial glial cells, isolated fibroblastic cells. For membranes was characterized by a positive reaction to GFAP and largely negative reaction (62.7%) on fibronectin, laminin. ERM in group II were more thick, which was in the range from 6,03±1,6 to 7.56±1,02 µm, high cell density: radial glial cells, cells of fibroblast series (fibroblasts laminocity, myofibroblasts) and hyalocity. Immunohistochemistry complicated ERM had a positive immunophenotyping antigens against adhesion protein fibronectin, laminin, of GFAP along with a pronounced fibroblastic and macrophage infiltration. Conclusion: ERM complicated lamellar macular hole, characterized by an increased thickness, marked infiltration of radial glial cells, cells of fibroblast series (fibroblasts laminocity, myofibroblasts) and hyalocity. The positive response comparable ERM complicated lamellar macular hole on fibronectin, laminin and GFAP could mean cytokines involved into development and progression of neurodegenerative process. The accumulation of collagen fibers and myofibroblasts may help to strengthen the contractions and reduce the elastic properties of ERM, with the subsequent development of the tangential tractions and retinal tear.Objective: Comparative morphological characteristic and evaluation of cytokine profile of idiopathic epiretinal membrane (ERM), complicated lamellar macular hole. Materials and Methods: Immunohistochemical study of 15 ERM removed during vitrectomy included the definition of responses to antigens fibronectin, laminin, glial fibrillary acidic protein. All membrane samples were divided into two groups: I group consisted of 8 ERM, which wasn’t clinically combined with retina defects, the II group included 7 ERM complicated lamellar macular hole. Results: ERM in group I were a collagen-membrane with a thickness from 2,1±0,7 to 4,4±1,4 µm, infiltrated radial glial cells, isolated fibroblastic cells. For membranes was characterized by a positive reaction to GFAP and largely negative reaction (62.7%) on fibronectin, laminin. ERM in group II were more thick, which was in the range from 6,03±1,6 to 7.56±1,02 µm, high cell density: radial glial cells, cells of fibroblast series (fibroblasts laminocity, myofibroblasts) and hyalocity. Immunohistochemistry complicated ERM had a positive immunophenotyping antigens against adhesion protein fibronectin, laminin, of GFAP along with a pronounced fibroblastic and macrophage infiltration. Conclusion: ERM complicated lamellar macular hole, characterized by an increased thickness, marked infiltration of radial glial cells, cells of fibroblast series (fibroblasts laminocity, myofibroblasts) and hyalocity. The positive response comparable ERM complicated lamellar macular hole on fibronectin, laminin and GFAP could mean cytokines involved into development and progression of neurodegenerative process. The accumulation of collagen fibers and myofibroblasts may help to strengthen the contractions and reduce the elastic properties of ERM, with the subsequent development of the tangential tractions and retinal tear.